Clear Cell Papillary Renal Cell Carcinoma and Renal Angiomyoadenomatous Tumor: Two Variants of a Morphologic, Immunohistochemical, and Genetic Distinct Entity of Renal Cell Carcinoma. (July 2015) - Deml, Karl-Friedrich; Schildhaus, Hans-Ulrich; Compérat, Eva; von Teichman, Adriana; Storz, Martina; Schraml, Peter; Bonventre, Joseph V.; Fend, Falko; Fleige, Barbara; Nerlich, Andreas; Gabbert, Helmut E.; GaBler, Nikolaus; et al.
Abstract : Clear cell papillary renal cell carcinoma (ccpRCC) and renal angiomyoadenomatous tumor (RAT) share morphologic similarities with clear cell (ccRCC) and papillary RCC (pRCC). It is a matter of controversy whether their morphologic, immunophenotypic, and molecular features allow the definition of a separate renal carcinoma entity. The aim of our project was to investigate specific renal immunohistochemical biomarkers involved in the hypoxia-inducible factor pathway and mutations in the VHL gene to clarify the relationship between ccpRCC and RAT. We investigated 28 ccpRCC and 9 RAT samples by immunohistochemistry using 25 markers. VHL gene mutations and allele losses were investigated by Sanger sequencing and fluorescence in situ hybridization. Clinical follow-up data were obtained for a subset of the patients. No tumor recurrence or tumor-related death was observed in any of the patients. Immunohistochemistry and molecular analyses led to the reclassification of 3 tumors as ccRCC and TFE3 translocation carcinomas. The immunohistochemical profile of ccpRCC and RAT samples was very similar but not identical, differing from both ccRCC and pRCC. Especially, the parafibromin and hKIM-1 expression exhibited differences in ccpRCC/RAT compared with ccRCC and pRCC. Genetic analysis revealed VHL mutations in 2/27 (7%) and 1/7 (14%) ccpRCC and RAT samples, respectively. Fluorescence in situ hybridization analysis disclosed a 3p loss in 2/20 (10%) ccpRCC samples. ccpRCC and RAT have a specific morphologic and immunohistochemical profile, but they share similarities with the more aggressive renal tumors. On the basis of our results, we regard ccpRCC/RAT as a distinct entity of RCCs.